Driving continuous process safety improvement from investigated incidents (Wiley, 2021)
"Companies handling hazardous materials and energies are always seeking to improve their process safety performance. Whether the reader is in the oil and gas, refining, petrochemical, chemical, or pharmaceutical industries, this book will provide guidance on learning from past incidents without have to experience the consequences from the incident. The learning models in this book describe scenarios showing how learning from publicly investigated incidents can assist manufacturers successfully improve their process safety performance, as well as improving four other main business-driven metrics at the same time: Personnel safety performance; Environmental responsibility; Product quality performance; and Sustainable long-term profitability. When lessons learned are shared and applied, process safety performance improves without a company having to learn significant lessons the hard way--in particular, through a significant incident that causes harm to people, the environment, and property"--